Real-World Exploration Increases Across Adolescence and Relates to Affect, Risk Taking, and Social Connectivity - Saragosa-Harris, Natalie M.; Cohen, Alexandra O.; Reneau, Travis R.; Villano, William J.; Heller, Aaron S.; Hartley, Catherine A. (Psychological Science, 2022)
Cross-species research suggests that exploratory behaviors increase during adolescence and relate to the social, affective, and risky behaviors characteristic of this developmental stage. However, how these typical adolescent behaviors manifest and relate in real-world settings remains unclear. Using geolocation tracking to quantify exploration—variability in daily movement patterns—over a 3-month period in 58 adolescents and adults (ages 13–27) in New York City, we investigated whether daily exploration varied with age and whether exploration related to social connectivity, risk taking, and momentary positive affect. In our cross-sectional sample, we found an association between daily exploration and age, with individuals near the transition to legal adulthood exhibiting the highest exploration levels. Days of higher exploration were associated with greater positive affect irrespective of age. Higher mean exploration was associated with greater social connectivity in all participants but was linked to higher risk taking selectively among adolescents. Our results highlight the interplay of exploration and socioemotional behaviors across development and suggest that societal norms may modulate their expression in naturalistic contexts.